Use of Antioxidants in Chicken Nuggets Manufactured with and Without the Use of Salt and/or Sodium Tripolyphosphate: Effects on Product Quality and Shelf-life Stability - O`Sullivan, Clare Maria; Lynch, Anna-Marie; Lynch, Patrick Brendan; Buckley, Denis Joseph; Kerry, Joseph Patrick (International Journal of Poultry Science, 2004)
Nuggets were manufactured from equal portions of breast and thigh chicken meat from chickens fed either a basal (control) or a supplemented level of alpha-tocopheryl acetate (vitamin E). Rosemary (0.10%) (R), sage (0.10%) (S) and tea catechins (0.01%) (TC), which were chosen from previous screening trials, were added to both control and vitamin E meat from which chicken nuggets were manufactured. The trial was repeated twice more where in addition to antioxidant addition to meat prior to nugget manufacture, 0.75% salt and 0.75% salt and 0.25% sodium tripolyphosphate (STPP) were also incorporated into both control and supplemented minced meat. Nuggets were tested for oxidative (TBARS) stability, colour (Hunter ´L, a, b` values) stability and percentage cook loss. There was a synergism between vitamin E and added antioxidants as nuggets containing vitamin E with R, S or TC had lower TBARS values than those containing vitamin E alone. Control nuggets containing R, S and TC had lower (p